2013
DOI: 10.1093/bja/aet065
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ropivacaine concentrations during bilateral transversus abdominis plane infusions

Abstract: Given the potential for high plasma concentrations from a bilateral TAP infusion technique, attention should be paid to individualized dosing strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 23 publications
(26 reference statements)
3
26
0
2
Order By: Relevance
“…Fifty cases of toxicity occurred after a single injection of LA, whereas in 8 cases, signs and symptoms arose during continuous infusion of LA. 35,38,40,41,54,55,58 In 7 cases, toxicity followed topical administration of LA without needle injection. 26,45,47,48,50,57,59 Finally, in 2 cases, LAST followed direct unintentional LA intravascular injection through a venous cannula.…”
Section: Setting Of Lastmentioning
confidence: 99%
“…Fifty cases of toxicity occurred after a single injection of LA, whereas in 8 cases, signs and symptoms arose during continuous infusion of LA. 35,38,40,41,54,55,58 In 7 cases, toxicity followed topical administration of LA without needle injection. 26,45,47,48,50,57,59 Finally, in 2 cases, LAST followed direct unintentional LA intravascular injection through a venous cannula.…”
Section: Setting Of Lastmentioning
confidence: 99%
“…Pharmacokinetic investigations of drugs used in TAP block are limited to 5 studies. [9][10][11][12][13] Four of these [9][10][11][12] studies have all considered the total local anesthetic concentration in plasma after single bolus TAP block. One of these studies 9 showed potentially toxic total plasma concentrations of lidocaine after 15 minutes; the other 3 studies 10-12 monitored ROP concentrations after single bolus dose.…”
Section: Introductionmentioning
confidence: 99%
“…Local anesthetic systemic toxicity has been reported following TAP blocks, 13,25 and it appears that doses used in clinical practice produce peak plasma concentrations that often exceed threshold levels associated with toxicity. 26,27 The risk of LAST with TAP blocks is significant for several reasons: large injection volumes (C 20 mL per side in adults) are used to ensure adequate spread, bilateral blocks are often performed to cover midline incisions, and the TAP contains a rich network of vessels. In addition, these blocks are commonly performed for post-Cesarean delivery analgesia, and as discussed, these patients may be more susceptible to LAST.…”
Section: Block Site and Techniquementioning
confidence: 99%
“…On a rapporté des cas de TSAL après des TAP, 13,25 et il semble que les doses utilisées dans la pratique clinique produisent des concentrations plasmatiques maximales qui dépassent souvent les seuils associés à une toxicité. 26,27 Lorsqu'on réalise un TAP, le risque de TSAL est considérable pour plusieurs raisons : d'importants volumes d'injection (C 20 mL par côté chez l'adulte) sont utilisés afin de garantir une bonne diffusion de l'AL, on réalise souvent des blocs bilatéraux afin de couvrir des incisions médianes, et le muscle transverse de l'abdomen contient un vaste réseau de vaisseaux. En outre, on réalise souvent ces blocs pour l'analgésie après un accouchement par césarienne et, comme mentionné plus haut, ces patientes pourraient être plus susceptibles à une TSAL.…”
Section: Grossesseunclassified